PENGARUH TARIF PAJAK EFEKTIF, TUNNELING INCENTIVE, MEKANISME BONUS, DAN EXCHANGE RATE TERHADAP TRANSFER PRICING ( STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2022) - Yudi Partama Putra; Kusuma Putri, Novita (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the influence of bonus mechanisms, taxes, tunneling incentives, exchange rates, and company size on transfer pricing practices in manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2022 period. The research method used is a quantitative method with a logistic regression approach, where the sample was determined through purposive sampling of 47 companies that met the criteria. The results show that the variables of bonus mechanisms, taxes, and tunneling incentives have a significant effect on transfer pricing practices, while exchange rates and company size have no significant effect. The conclusion of this study is that managerial incentives and fiscal pressure play an important role in encouraging companies to practice transfer pricing, while exchange rate fluctuations and company scale are not dominant factors. Keywords: Transfer Pricing, Bonus Mechanisms, Taxes, Tunneling Incentives, Exchange Rates